Xception fault injection and robustness testing framework: a case-study of testing RTEMS - Maia, R.; Henriques, L.; Barbosa, R.; Costa, D.; Madeira, H. (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2005: Anais do VI Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2005.23368, 2005)
Xception is an automated and comprehensive fault injection and robustness testing environment that enables accurate and flexible V&V (verification & validation) and evaluation of mission and business critical computer systems and computer components, with particular emphasis to software components. In this paper we focus on the new robustness testing features of Xception and illustrate them with a concrete example of robustness testing of the Real Time Executive for Multiprocessor Systems (RTEMS) performed under a European Space Agency (ESA) contract. To the best of our knowledge, this is the first time that robustness testing results for this real time operating system are presented. The testing revealed a significant number of critical flaws in RTEMS 4.5.0 and shows the effectiveness of Xception toolset.